Liver Disease in Clinical Practice - Cross, Tim (Springer International Publishing : Imprint: Springer, 2017)
This pocket guide covers the common manifestations of liver disease, how to treat them and when to refer patients on to specialist centers. The book outlines the common clinical liver diseases such as fatty liver disease and hepatitis, among others, and their current up to date management. Written by experts in the field and containing figures and tables, as well as case histories and questions, this is an enjoyable and reader-friendly book for the busy physician. With its authoritative, didactic style and short chapters, it covers the common presentations and complications of liver disease, and how to deal with them. Given the increasing prevalence of liver disease in the UK and throughout Western Europe, this is an ideal reference book for primary care physicians, doctors in specialist training, clinical nurse specialists and for gastroenterologists, who see patients with liver disease in their working lives.
Keywords: Medicine.; Gastroenterology.; Hepatology.; Nursing.; Primary care (Medicine).; elektronické knihy; electronic books